Do riders who wear an air jacket in equestrian eventing have reduced injury risk in falls? A retrospective data analysis - Nylund, L. E.; Sinclair, P. J.; Hitchens, P. L.; Cobley, S. (Journal of Science and Medicine in Sport, 2020)
In our original article, we identified that riders who wore an air jacket had 1.7 times increased odds of serious or fatal injury in falls compared to riders who were not wearing an air jacket.1 Since publication, a concern was raised by a reader, relating to the inclusion of data from all three disciplines of eventing competition. The reader pointed out that air jackets are only worn in the cross country discipline and that falls and injury severity are higher in this discipline than they are in showjumping or dressage.